Latinx College Students: How Schemas and Attachments Impact Depression and Relationship Satisfaction. Issue 2 (May 2020) - Rodriguez, Adrian; Ratanasiripong, Paul; Hardaway, Kimberly; Barron, Leslie; Toyama, Shiho
Latinx college students face challenges regarding depression. The relationships between early maladaptive schemas (EMS) and attachment style on depression and relationship satisfaction were investigated among 236 Latinx college student participants. The Young Schema Questionnaire–Short Form (YSQ-S3) total score was utilized to identify overall schema. Significant correlations were found. Overall schema, attachment anxiety, attachment avoidance, and depression were all positively correlated, while attachment anxiety, attachment avoidance, and depression were negatively correlated with relationship satisfaction. In multiple regression analyses, Model 1, overall schema and attachment anxiety significantly predicted depression. In Model 2, overall schema, attachment anxiety, and attachment avoidance significantly predicted relationship satisfaction, with EMS acting as a positive predictor. Results suggest that Latinx college students with EMS and anxious attachment style endorse more depression, while the influence of EMS and attachment style on relationship satisfaction needs to be further investigated. Considerations for the use of schema therapy and future research are discussed.